2023
DOI: 10.3389/fmicb.2023.1137932
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and antimicrobial susceptibility of human Brucella in Northeast China

Abstract: IntroductionNortheast China has always been an area with severe brucellosis prevalence. This study will identify Brucella in Northeast China and test its resistance to antibiotics, in order to clarify its resistance mechanism. Brucella is a widespread and highly pathogenic bacteria that poses serious threats to public health and animal husbandry.MethodsIn this study, 61 Brucella isolates were identified by abortus-melitensis-ovis-suis polymerase chain reaction (AMOS-PCR) for biotypes and epidemic potential was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The decision was to use a combination treatment with Rifampin (aminoglycoside), Doxycycline, and Cefotaxime for this patient to reduce the risk of deterioration. However, Trimethoprim-sulfamethoxazole (TMP-SMZ) is a combination antibiotic that may be used as an alternative treatment option for brucellosis [ 9 ]. Cefotaxime and TMP-SMZ were equally effective, and no clear preference existed for one.…”
Section: Discussionmentioning
confidence: 99%
“…The decision was to use a combination treatment with Rifampin (aminoglycoside), Doxycycline, and Cefotaxime for this patient to reduce the risk of deterioration. However, Trimethoprim-sulfamethoxazole (TMP-SMZ) is a combination antibiotic that may be used as an alternative treatment option for brucellosis [ 9 ]. Cefotaxime and TMP-SMZ were equally effective, and no clear preference existed for one.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, resistance rates to antibiotics, which are the main choice for brucellosis treatment, are on the rise. A recent study found that 24.6% of Brucella isolates collected in northeast China were resistant to rifampicin [ 58 ]. In Bosnia and Herzegovina, 84.3% of Brucella isolates sampled from human patients were resistant to trimethoprim-sulfamethoxazole [ 59 ].…”
Section: Bacterial Zoonotic Infectionsmentioning
confidence: 99%